PEMBERDAYAAN ANAK DAN REMAJA DI DESA PESISIR MELALUI ENGLISH FOR TOURISM - Serly Susanti Penton (JA (Jurnal Abdiku) : Jurnal Pengabdian Kepada Masyarakat, 2024)
The English language training for children and teenagers in Retta, South Pura village, Pura district, Alor regency aims to enhance their communication skills in preparation for opportunities in tourism sector. This training was conducted for three days, from October 26 – 28, 2024, at GMIT Bethel Retta church. Various learning methods were employed, including group discussions, presentations, simulations, and interactive conversation practice. The training materials covered basic English, effective communication techniques, and role-playing to build participants’ confidence in using English. This activity involved various stakeholders and was supported by English study program students as group facilitators. The results of the training indicate that participants experienced an improvement in their understanding and communication skills in English. Additionally, there was an increase in confidence in speaking and a higher enthusiasm for learning among the participants. This training is expected to serve as an initial step in developing local human resources who are ready to compete in the tourism industry.